2014
DOI: 10.1002/biot.201400283
|View full text |Cite
|
Sign up to set email alerts
|

A combination of targeted toxin technology and the piggyBac‐mediated gene transfer system enables efficient isolation of stable transfectants in nonhuman mammalian cells

Abstract: Isolation of cells harboring exogenous DNA is typically achieved by the introduction of plasmids, but its efficiency remains still low. In this study, we developed a novel strategy to obtain stable transfectants efficiently. Porcine embryonic fibroblasts were transfected with two plasmids: (i) pTransIEnd, which comprises the ubiquitous promoter, the piggyBac (PB) transposase gene, an internal ribosomal entry site, the Clostridium perfringens-derived endo-β-galactosidase C (EndoGalC) gene, and a poly(A) tail an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 36 publications
(51 reference statements)
0
13
0
Order By: Relevance
“…The PB-based transposons and PB expression plasmid used in the present study are shown in Figure 1A. Briefly, the pTrans (pCX-mPB) vector [37] confers expression of the PB transposase gene under the control of CAG , a chicken β-actin-based systemic promoter [38]. pT-pac is a transposon vector carrying a puromycin acetyltransferase gene ( pac ) expression unit linked to the mouse phosphoglycerate kinase ( Pgk ) promoter [37].…”
Section: Resultsmentioning
confidence: 99%
“…The PB-based transposons and PB expression plasmid used in the present study are shown in Figure 1A. Briefly, the pTrans (pCX-mPB) vector [37] confers expression of the PB transposase gene under the control of CAG , a chicken β-actin-based systemic promoter [38]. pT-pac is a transposon vector carrying a puromycin acetyltransferase gene ( pac ) expression unit linked to the mouse phosphoglycerate kinase ( Pgk ) promoter [37].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, cells surviving after IB4SAP treatment must be those exhibiting strong expression of EndoGalC (as well as CRISPR/Cas9-related components), although its expression was transient. Notably, Sato et al [ 23 , 24 ] demonstrated that high expression levels of EndoGalC (evaluated by the loss of the α-Gal epitope) are closely associated with those of GFP from the co-transfected expression vector. From these present studies, our targeted toxin-based cell selection system was found to be more effective for the enrichment of bi-allelic KO clones than the conventional puromycin-based cell selection system.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, cells transfected with an EndoGalC expression vector fail to react with IB4 [ 22 ]. Using this unique inverse-relationship between decreased reactivity to IB4 and increased EndoGalC expression, Sato et al [ 23 , 24 ] developed a novel drug-free selection system for genetically modified cells. Based on the background of this study, we developed a novel CRISPR/Cas9-based approach to enrich genome-edited non-human cells having bi-allelic KO alleles in a drug-free condition.…”
Section: Introductionmentioning
confidence: 99%
“…Two PB expression plasmids pT-EGFP ( Figure 1 A) and pT-CETD ( Figure 2 A) were generated using pPB (pPB-MCS-P5), a plasmid carrying two PB acceptors with inverted repeats, as a basal plasmid. pT-EGFP carries an EGFP gene expression unit (CAG + EGFP cDNA + poly(A) sites) [ 62 ]. pT-CETD confers gene switching from EGFP cDNA to the DT-A gene when Cre expression occurs, as previously discussed [ 37 ].…”
Section: Methodsmentioning
confidence: 99%